2022
DOI: 10.1039/d2ta02495k
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the electrochemical reaction mechanisms of precious metals Au and Ru as cathode catalysts in Li–CO2 batteries

Abstract: The electrochemical reaction mechanisms of Au and Ru as cathode catalysts in Li-CO2 batteries are firstly studied by First-principles density functional theory (DFT) calculations. During the discharging process, the free...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…Unveiling mechanisms are essential for advancing catalyst design. Recently, many efforts have been made to reveal the mechanism of Li–CO 2 batteries based on experimental characterizations and theoretical calculations, but the reaction mechanism remains controversial. For example, the reaction of *CO + CO 2 → *CO 3 + C has been suggested as a critical step for the generations of Li 2 CO 3 and C. However, such a step is actually infeasible because of its relatively high energy barriers. , Besides the conventional product of Li 2 CO 3 , many other Li-containing discharge products were also detected experimentally. For instance, Li 2 C 2 O 4 has been identified as the final discharge product for Mo 2 C-based catalysts. , In contrast, Li 2 C 2 O 4 was observed as a reaction intermediate (rather than the final product) in the initial discharge stage over Au and porous carbon catalysts.…”
mentioning
confidence: 99%
“…Unveiling mechanisms are essential for advancing catalyst design. Recently, many efforts have been made to reveal the mechanism of Li–CO 2 batteries based on experimental characterizations and theoretical calculations, but the reaction mechanism remains controversial. For example, the reaction of *CO + CO 2 → *CO 3 + C has been suggested as a critical step for the generations of Li 2 CO 3 and C. However, such a step is actually infeasible because of its relatively high energy barriers. , Besides the conventional product of Li 2 CO 3 , many other Li-containing discharge products were also detected experimentally. For instance, Li 2 C 2 O 4 has been identified as the final discharge product for Mo 2 C-based catalysts. , In contrast, Li 2 C 2 O 4 was observed as a reaction intermediate (rather than the final product) in the initial discharge stage over Au and porous carbon catalysts.…”
mentioning
confidence: 99%
“…5). 44,47 We also studied the possibility of MgCO 3 formation along with C and CO 2 from CO splitting and found that the calculated Gibbs free energy of CO disproportionation is 1.72 eV. Overall, the free energy changes for the rate-controlling step of the first splitting reactions in (1) and (2) are −1.54 eV and 0.19, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…The interatomic distances between C and the surface atoms are significantly shorter (1.450 Å) than that of O (2.309 Å) in CO 2 , and the adsorption of CO 2 exhibits a proclivity to form a “V” configuration, which is consistent with previous experimental and theoretical studies. 45–48 Upon closer inspection, we found that the adsorbed CO 2 onto the catalytic surface resulted in a twisted angle of 130° between the two CO bonds. Additionally, the CO bond distance was significantly elongated, from 1.176 Å in the gas phase to 1.286 Å on α-Mo 2 C (001).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations